UNDERSTANDING AUTISM: AN INTRODUCTION FOR PARENTS - SACHIN KUMAR; AMIT KUMAR; ABHISHEK SINGH (International Journal of Pharma and Bio Sciences, 2010)
Autism is currently estimated to affect approximately one in every 166 children, yet the cause or causes of the condition are not well understood. One of the current theories concerning the condition is that among a set of children vulnerable to developing the condition because of their underlying genetics. Autism is a developmental disability that affects how the brain function specifically those areas of the brain that control social ability and communication skills. Boys are more likely to develop autism, and most children are diagnosed before the age of 3. Children and adults with autism typically have difficulty in both verbal and nonverbal communication. People with autism may have a difficult time relating to the outside world and may have unusual reactions to the people around them. People with autism may demonstrate aggressive behavior that may cause injury to themselves or others. The disorder also may cause sensitivity to the senses of sight, hearing, touch, smell, and taste. Occupational therapy can provide intervention that helps children to develop appropriate social, play, and learning skills. The therapist aids the child in achieving and maintaining normal daily tasks such as getting dressed and playing with other children.